Diseño urbano para readecuación y generación de espacio colectivo y de accesibilidad en Villa Valentina II (2023)
In this final degree work, research was implemented for the development of social mapping that aims to understand the shortcomings of a territory seeking the participation of the community through strategies for the integral improvement of neighborhoods. In the sector of Villa Valentina II, a territory with an absence of social spaces, irregular morphology, environmental and social problems and consolidated residual public spaces was diagnosed.